The Neuroprotective Effect of Hemin and the Related Mechanism in Sevoflurane Exposed Neonatal Rats - Yang, Fan; Shan, Yangyang; Tang, Zhiyin; Wu, Xiuying; Bi, Congjie; Zhang, Yongfang; Gao, Yan; Liu, Hongtao (Frontiers in Neuroscience, 2019)
Background: Many studies have reported that sevoﬂurane can increase neuronal apoptosis and result in cognitive deficits in rodents. Although neurotoxicity may be associated with mitochondrial dysfunction and oxidative stress, the exact mechanism remains unclear. In order to evaluate potential treatment therapies, we studied the effects of hemin on neurotoxicity of neonatal rat sevoflurane exposure. Methods: Postnatal day (P) 7 rats were assigned randomly to four groups; (1) group C: non-anesthesia, (2) group H: intraperitoneal hemin (50 mg kg-1) treatment on days 5 and 6, (3) group S: 3% sevoﬂurane exposure for 4 h, and (4) group SH: hemin treatment + sevoﬂurane exposure. The expression of neuroglobin in neonatal hippocampus was determined by western blot and immunohistochemistry. Neuroglobin was localized by immunofluorescence. Western blot for the expression of cleaved caspase-3 and TUNAL were used to detect neonatal hippocampal apoptosis, and cytochrome c was used to evaluate mitochondrial function. Drp-1 and Mfn-2 immunoblotting were used to assess mitochondrial dynamics. The Morris water maze test was performed to detect cognitive function in the rats on P30. Results: Exposure to sevoflurane increased the expression of cleaved caspase-3, cytochrome c, and Drp1 in the neonatal hippocampus and resulted in cognitive deficiency but decreased expression of Mfn2. Hemin reduced apoptosis, improved mitochondrial dynamics and ameliorated the cognitive impairment caused by sevoflurane exposure. Conclusions: Hemin reduced neuronal apoptosis, improved mitochondrial dynamics and protected against cognitive deficits induced by sevoflurane in neonatal rats. This neuroprotective effect may be achieved by increasing the expression of neuroglobin.